2015
DOI: 10.1270/jsbbs.65.26
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of potato genetic resources

Abstract: A considerable number of highly diverse species exist in genus Solanum. Because they can adapt to a broad range of habitats, potato wild relatives are promising sources of desirable agricultural traits. Potato taxonomy is quite complex because of introgression, interspecific hybridization, auto- and allopolyploidy, sexual compatibility among many species, a mixture of sexual and asexual reproduction, possible recent species divergence, phenotypic plasticity, and the consequent high morphological similarity amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 113 publications
3
83
0
10
Order By: Relevance
“…This study also revealed the value of hardy wild relatives of quinoa, cañahua, and potato as famine foods for Altiplano communities in periods of climate stress. The high glycoalkaloid content of S. juzepczukii and S. curtilobum inherited from their wild progenitors confers resistance to pests and diseases (Tingey 1984;Machida-Hirano 2015). Nonetheless, in this study, farmers observed that due to rising temperatures, S. juzepczukii is starting to be affected by pests.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This study also revealed the value of hardy wild relatives of quinoa, cañahua, and potato as famine foods for Altiplano communities in periods of climate stress. The high glycoalkaloid content of S. juzepczukii and S. curtilobum inherited from their wild progenitors confers resistance to pests and diseases (Tingey 1984;Machida-Hirano 2015). Nonetheless, in this study, farmers observed that due to rising temperatures, S. juzepczukii is starting to be affected by pests.…”
Section: Discussionmentioning
confidence: 65%
“…The latter species are known for their frost and drought tolerance and are also recognized for resistance to insect pests and late blight (Phytophthora infestans) (Martinez et al 2001;Browman 2003;Baldinelli 2014;Condori et al 2014). The frost tolerance of S. juzepczukii, S. curtilobum, and S. ajanhuiri can be traced to their wild progenitors: S. acaule and S. bolivense (Rodríguez et al 2010;Ovchinnikova et al 2011;Machida-Hirano 2015). Gene flow between wild and cultivated types is an important element of crop adaptation in their centres of origin (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В «Атласе диких видов картофеля» приведены морфологические описания и све-дения о географии местообитаний 196 видов картофеля (Hijmans et al, 2002). Для установления филогенетических отношений между клубнеобразующими видами Solanum использованы молекулярные методы генотипирования (Spooner et al, 2014;Machida-Hirano, 2015). Однако до настоящего времени нет общепризнанной классификации этих видов.…”
Section: скрещиваемость диких и культурных видов картофеляunclassified
“…Вопросам классификации клубненосных видов Sola num L., решаемым с помощью молекулярного и геномного анализа, посвящены работы (Jacobs et al, 2008(Jacobs et al, , 2011Bradeen, Haynes, 2011;Spooner et al, 2014;MachidaHirano, 2015). Родственные взаимоотношения и таксономия ви дов картофеля продолжают оставаться дискуссионными.…”
Section: систематика картофеляunclassified